Pengembangan Media Pembelajaran Berdiferensiasi Berbasis Teknologi pada Materi Teks Prosedur untuk Siswa Kelas VII SMP - Prillia Ekaningtiass; Herni Fitriani; Muhammad Nanang Nurudin; Sulistina Akhodiyah (Departement of Mathematics Education, 2023)
Differentiated learning in the independent curriculum requires teachers to use learning media according to the type of student learning style. This study aims to develop differentiated learning media on procedural text material for grade VII junior high school. The research method used is the Research and Development (R&D) method according to Borg and Gall which consists of 4 levels of development. This development research only reaches level 1, namely producing product designs and not continuing for testing. The results showed that the percentage of validation results from media experts, material experts, and practitioner experts with an average rating of 88.43% was in the valid category. Based on the results of the study it can be concluded that the technology-based differentiated learning media is valid for use in procedural text material for class VII